PENGARUH EMPLOYEE ENGAGEMENT TERHADAP KINERJA KARYAWAN YANG DI MEDIASI KEPUASAN KERJA - Dwi Astuti; Suwandi Suwandi (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Employee engagement is a condition in which employees feel actively involved and attached to the organization where they work. Job satisfaction is a positive feeling felt by employees towards their work. Employee performance is the level of productivity and effectiveness achieved by employees in carrying out their work. This study aims to examine the effect of employee engagement on employee performance which is mediated by job satisfaction. The population in this study are all employees in a company. The sampling technique used was random sampling with a total sample of 72 employees. The results of the study show that employee engagement has a positive and significant effect on employee job satisfaction. Job satisfaction has a positive and significant effect on employee performance. And employee engagement also has a positive and significant effect on employee performance through job satisfaction. The conclusion from this study is that employee engagement has a positive effect on employee performance through job satisfaction. Therefore, companies need to improve employee engagement to improve employee performance through job satisfaction.